2020
DOI: 10.1101/2020.05.23.20111559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating Household Transmission of SARS-CoV-2

Abstract: **Introduction and Goals.** SARS-CoV-2 is transmitted both in the community and within households. Social distancing and lockdowns reduce community transmission but do not directly address household transmission. We provide quantitative measures of household transmission based on empirical data, and estimate the contribution of households to overall spread. We highlight policy implications from our analysis of household transmission, and more generally, of changes in contact patterns under social distancing. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 41 publications
(72 reference statements)
1
37
0
Order By: Relevance
“… 79 Modeling studies demonstrated that household transmission had a greater impact on R after social distancing (30%–55%) compared to before social distancing (5%–35%). 80 …”
Section: Discussionmentioning
confidence: 99%
“… 79 Modeling studies demonstrated that household transmission had a greater impact on R after social distancing (30%–55%) compared to before social distancing (5%–35%). 80 …”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies were conducted in Asia, and some in Europe and the United States. [4][5][6][8][9][10] Madewell et al 4 , Lei et al 6 , and Curmei et al 5 conducted meta-analyses of previous studies and found pooled household SARs of 19% (95% CI: 15% -23%), 27% (21% -32%), and 30% (18% -43%), respectively. Some of the included studies compared SARs in household settings verses non-household settings, and pooled estimates found that household SARs were five 4 to ten 6 times as high as non-household SARs, which highlights the role of household transmission in the spread of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…R base models transmission that is not correlated with activity at POIs in the SafeGraph dataset, including within-household transmission and transmission at POI categories which are not well-captured in the SafeGraph dataset. We chose the lower limit of 0.1 because beyond that point, base transmission would only contribute minimally to overall R, whereas previous work suggests that within-household transmission is a substantial contributor to overall transmission [60][61][62] . Household transmission alone is not estimated to be sufficient to tip overall R 0 above 1; for example, a single infected individual has been estimated to cause an average of 0.32 (0.22, 0.42) secondary within-household infections 60 .…”
Section: M41 Selecting Parameter Rangesmentioning
confidence: 99%
“…We chose the lower limit of 0.1 because beyond that point, base transmission would only contribute minimally to overall R, whereas previous work suggests that within-household transmission is a substantial contributor to overall transmission [60][61][62] . Household transmission alone is not estimated to be sufficient to tip overall R 0 above 1; for example, a single infected individual has been estimated to cause an average of 0.32 (0.22, 0.42) secondary within-household infections 60 . However, because R base may also capture transmission at POIs not captured in the SafeGraph dataset, to be conservative, we chose an upper limit of R base = 2; as we describe below, the best-fit models for all 10 metro area s have R base < 2, and 9 out of 10 have R base < 1.…”
Section: M41 Selecting Parameter Rangesmentioning
confidence: 99%